1993
DOI: 10.1164/ajrccm/147.5.1162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of One Night without Nasal CPAP Treatment on Sleep and Sleepiness in Patients with Obstructive Sleep Apnea

Abstract: Nasal continuous positive airway pressure (CPAP) has become the nonsurgical treatment of choice for obstructive sleep apnea syndrome (OSAS). Recent evidence suggests that intermittent use of CPAP by patients is more common than nightly compliance. To determine the consequences of intermittent CPAP use, in terms of a return of sleep-disordered breathing and daytime hypersomnolence, 15 OSAS subjects were evaluated at three times: (1) before CPAP treatment (pretreatment), (2) after 30 to 237 days posttreatment du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
168
0
10

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(187 citation statements)
references
References 33 publications
9
168
0
10
Order By: Relevance
“…22 There is no clear predictive factor for compliance. Although use of nCPAP every night has been shown to be optimal, 29 the minimum number of hours per night that is actually required to ameliorate OSAS symptoms is not known. Engleman et al 23 reported significant improvement in daytime symptoms with nCPAP, despite a mean machine run time of only 3.7 hours.…”
Section: Long-term Compliance With Continuous Positive Airway Pressurementioning
confidence: 99%
“…22 There is no clear predictive factor for compliance. Although use of nCPAP every night has been shown to be optimal, 29 the minimum number of hours per night that is actually required to ameliorate OSAS symptoms is not known. Engleman et al 23 reported significant improvement in daytime symptoms with nCPAP, despite a mean machine run time of only 3.7 hours.…”
Section: Long-term Compliance With Continuous Positive Airway Pressurementioning
confidence: 99%
“…The associated consequences include daytime sleepiness [3], decreased cognitive performance, decreased quality of life [4], increased risk of automobile and industrial accidents [5,6], and adverse cardiovascular sequelae [7][8][9][10]. Treatment of OSA leads to improvements in many of these adverse outcomes and may reduce healthcare costs [11][12][13]. Thus, diagnosis of this disorder is important.…”
Section: Introductionmentioning
confidence: 99%
“…Airflow obstruction is thought to result from decreases in pharyngeal neuromuscular activity at sleep onset (2). These episodes lead to intermittent hypoxemia and recurrent arousals from sleep, accounting for the long-term neurocognitive (3,4), metabolic (5), and cardiovascular (6) sequelae of this disorder. Nasal continuous positive airway pressure remains the mainstay of treatment for moderate to severe obstructive sleep apnea (7).…”
mentioning
confidence: 99%